การสื่อสารผ่าน เว็บ 2.0 เพื่อส่งเสริมทุนสร้างสรรค์ใน http://www.exteen.com และ http://www.bloggang.com - ธฤตวัน ไชยวสุ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research has the following objectives: to study how Thai creative entrepreneurs communicate their creative capital through web 2.0; to study the factors that influence the success of creative capital development through web 2.0 communications; to study how Thai creative entrepreneurs realize the intellectual property infringement from websites and study how Thai creative entrepreneurs who communicate through web 2.0 prevent their creative capital from the infringers. Ethnography research and in-depth interview were used as a data collection method for the case studies. The research finds that Thai creative entrepreneurs have 3 main ways to communicate their creative capital through web 2.0; promoting their information and creative capital; displaying and storing their work and exchanging comments, attitudes and their experiences with other bloggers. Upon examination of these events, it becomes clear that there are 2 main factors that influence the success of creative capital development through web 2.0 communications; unique technological factors of web 2.0 and online community factor which comes from commenting, chatting from chat box and promoting the creative capital. In regards to the intellectual property infringement, half of the Thai creative entrepreneurs from the research realize that Copyright Law and Creative Commons can prevent the intellectual property infringement from websites. All of the Exteen’s.